PARENTAL SOCIO-ECONOMIC BACKGROUND AND STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN IKOLOMANI SUB- COUNTY, KAKAMEGA COUNTY, KENYA - Madegwa, Brenda Muhavi; Piliyesi, Sr. Dr. Elizabeth; Katundano, Sr. Dr. Theonestina (Journal of Education and Practice, 2019)
Purpose: The purpose of this study was to investigate to what extent the socio- economic background of parents influence the academic performance of students in public secondary schools in Ikolomani Sub- County, Kakamega County. This study was guided by the following research questions: How does parental level of education influence students' performance? How does parental occupation level influence students' performance? How does parental income level influence students'performance? What are the socioeconomic challenges facing parents in enhancing students' academic performance in public secondary schools in lkolomani Sub-County? What are the possible solutions to enhance students' academic performance in public secondary schools in lkolomani Sub-County? Methodology: The study used both quantitative and qualitative research approaches. The study employed proportionate stratified random sampling to select the schools while purposive, cluster sampling and simple random sampling was used to select the students. Teachers were selected using stratified and simple random sampling. Principals, parents' representatives and Education officer were purposively selected. Data were collected using questionnaires, document analysis and interview guide. Qualitative and quantitative data were concurrently collected and analyzed. Statistical package for Social Science (SPSS version 23) was used to analyze quantitative data while qualitative data was analyzed thematically to obtain views and perceptions of the respondents. Results: The study found that parental socio-economic background played a key role in enhancement of students' academic performance. Recommendations: The study recommended that parents should be encouraged to start small income generating business so as to cater for the educational needs of their children.